The Relationship between Field Dependence-Independence and Reading Strategy toward Reading Comprehension - Rahmani, Bita Dwi (University of Muhammadiyah Prof. DR. HAMKA, 2016)
This study investigated the relationship between learning style (X1) and reading strategy (X2) toward reading comprehension (Y). The learning style is categorized into two: field independence (FI) and field dependence (FD). This study was carried out in one of the public senior high schools in Jakarta by using purposive sampling technique; 79 out of 120 students of science class in academic year 2008-2009 were chosen. The quantitative and qualitative methods were used to analyze the data. Questionnaires and one reading comprehension test were distributed to analyze the data quantitatively. The first instrument identified students belonging to FI or FD. The second instrument concerned with identifying the frequency of reading strategy that students mostly used. 20 numbers of reading comprehension test were given to measure the comprehension and strategy that they used. This study found that both learning style (X1) and reading strategy (X2) influenced the reading comprehension (Y). In other words, the more independent students are and the more frequent they use strategy, the greater they will comprehend the text. As a consequence, the findings suggest that teachers introduce various kinds of strategy in reading comprehension because every student needs particular strategy.